TOUR PACKAGE PURCHASING DECISION OF PT. ARAS HIJRAH TOUR AND TRAVEL PEKANBARU - Zanuba Khalila; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Currently the development of tourism in Indonesia is growing rapidly. The development of the tourism sector is considered promising and provides benefits to many parties ranging from government, society and the private sector. This is because tourism is an area that is considered to have the potential to be developed and can benefit one of them in the field of travel agencies. However, over time, technological advances have also developed rapidly, this has an impact on the travel bureau. Rapid technological advances have led to a decline in the number of sales at travel bureaus. Good airplane ticket sales and tour packages. Rapidly advancing technological advances do not affect everyone. This is evidenced in the increase in sales of tour packages at PT.Aras Hijrah Tour and Travel Pekanbaru. In this study, focusing on factors that influence the decision to purchase tour packages by consumers PT. Aras Hijrah Tour and Travel. The quantitative descriptive approach method can provide a detailed description of the problem under study. In this study, the authors distributed Questionnaire or Questionnaire to 100 respondents, with 12 questions. The results of this study prove that psychological decisions are an influential factor in making decision to purchase tour packages at PT. Aras Hijrah Tour and Travel Keywords: Tourism, Travel Bureau, Tour Packages, Purchasing Decisions.